The Effect Of Stator Excitation Current On The Driving Torque Of A Single-Phase “6/6” Switched Reluctance Generator Design With External Excitation - Simatupang, Gidion; Siagian, Parlin; Dalimunthe, Muhammad Erpandi (Jurnal Media Computer Science, 2026)
Switched Reluctance Generators (SRGs) have attracted attention due to their robust construction, low cost, and high fault tolerance, suitable for extreme environments. However, SRGs suffer from torque ripple and acoustic noise due to the non-linear torque-excitation current relationship. Although SRG component optimization has been investigated, a gap exists in the analysis of the effect of stator excitation current on the drive torque in a single-phase "6/6" SRG design with external amplification. This study analyzes the impact of varying stator excitation current on the drive torque of a single-phase 6/6 SRG. The methodology includes design, finite element analysis (FEA), and testing of an initial drive torque prototype. Results show that increasing the stator coil supply voltage results in a greater magnetic force, which counteracts the mechanical torque on the rotor shaft. This understanding is crucial for optimizing torque performance, mitigating ripple, and improving SRG efficiency for future applications.